Field notes contributed by Michael C. Dooley, summer 2000 - Dooley, Michael C.et al (2000)
Summer report of birds found in eastern Iowa contributed by Michael C. Dooley. This item was used as supporting documentation for the Iowa Ornithologists' Union Quarterly field report of summer 2000. Epson - sheet feed